PERAN MEDIA PEMBELAJARAN TERHADAP KINERJA DOSEN DENGAN GAYA KEPEMIMPINAN TRANSFORMASIONAL SEBAGAI VARIABEL MODERATING (Studi Kasus pada Dosen Universitas Muhammadiyah Ponorogo) - Eka D. Pristi Ayuningtyas; Wahna Widhianingrum (Universitas Muhammadiyah Ponorogo, 2017)
This study focuses on transformational leadership style variables that moderate the relationship between learning media and performance. This study aims to examine the role of learning media on lecturer performance with transformational leadership style as a moderating variable. This type of research is a quantitative research. The method used is to use survey with purposive sampling sampling with respondent Lecturer Muhammadiyah University of Ponorogo. Data analysis technique used in this research is Structural Equational Modeling Partial Least Square (SEM-PLS) analysis with SmartPLS 3.0 software. The result of research shows that H1, the perception of the usefulness of instructional media has a negative effect on overwork. While H2, the transformational leadership style variables moderate the relationship between perceptions of the usefulness of instructional media and overloaded work